2019
DOI: 10.1038/s41419-019-1849-x
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol induces cytoprotective autophagy via blocking the Akt/mTOR pathway in ovarian cancer cells

Abstract: Paeonol (Pae), a phenolic acid compound isolated from the Moutan Cortex, was previously demonstrated to exert multiple anticancer effects. The rational control of autophagy has been considered a potential treatment strategy for epithelial ovarian cancer. However, whether Pae induces autophagy and the relationship between its antitumour activities and autophagy in epithelial ovarian cancer are still unclear. In this study, we found that Pae induced not only antiproliferation activity and apoptosis but also auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 45 publications
(58 reference statements)
3
44
0
Order By: Relevance
“…ROS, small and highly reactive molecules, are the normal metabolite products of mitochondria, and ROS overproduction serves as an important mediator in cell death in response to various stimuli [33][34][35] . Accumulating evidence has indicated that excessive ROS generation contributes to cell cycle arrest and mitochondriadependent apoptosis 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS, small and highly reactive molecules, are the normal metabolite products of mitochondria, and ROS overproduction serves as an important mediator in cell death in response to various stimuli [33][34][35] . Accumulating evidence has indicated that excessive ROS generation contributes to cell cycle arrest and mitochondriadependent apoptosis 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…TEM assay was performed as described previously 23 . Briefly, alteronol-treated A375 cells were harvested and fixed in 0.1 M sodium cacodylate buffer containing 2.5% glutaraldehyde at 4°C and post-fixed with 1% osmium tetroxide for 3 h. The sample was dehydrated and embedded in EMbed 812 (Electron Microscopy Sciences).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…The accumulation of LC3-II can be interpreted as indicating excessive autophagosome formation or reduced degradation. To clarify this, a flux experiment was performed with a tandem mRFP-GFP-LC3 adenovirus, a reporter used to conveniently monitor and quantify autophagy flux 42 . The mRFP signal was relatively stable compared with that of GFP, since functional fusion with the lysosome allows quenching of the acid-sensitive GFP signal (Fig.…”
Section: Nnc-55 Promotes Autophagosome Formation But Blocks Distal Aumentioning
confidence: 99%